An Observational, Prospective, Multicenter, Registry-Based Cohort Study Comparing Conservative and Medical Management for Patent Ductus Arteriosus - Okulu, Emel; Erdeve, Omer; Arslan, Zehra; Demirel, Nihal; Kaya, Huseyin; Gokce, Ismail Kursad; Ertugrul, Sabahattin; Cetinkaya, Merih; Buyukkale, Gokhan; Ozlu, Ferda; Simsek, Huseyin; Celik, Yalcin; et al. (Frontiers in Pediatrics, 2020)
No consensus has been reached on which patent ductus arteriosus (PDAs) in preterm infants require treatment and if so, how and when they should be treated. A prospective, multicenter, cohort study was conducted to compare the effects of conservative approaches and medical treatment options on ductal closure at discharge, surgical ligation, prematurity-related morbidities and mortality. Infants between 240/7–286/7 weeks of gestation from 24 neonatal intensive care units were enrolled. Data on PDA management and patients’ clinical characteristics were recorded prospectively. Patients with moderate-to-large PDA were compared. Among the 1,193 enrolled infants (26.7±1.4 wk and 926±243 g), 649 (54%) had no or small PDA, whereas 544 (46%) had moderate-to-large PDA. One hundred thirty (24%) infants with moderate-to-large PDA were managed conservatively, in contrast to 414 (76%) who received medical treatment. Eighty (62%) of 130 infants who were managed conservatively did not receive any rescue treatment and the PDA closure rate was 53% at discharge. There were no differences in the rates of late-onset sepsis, necrotizing enterocolitis (NEC), retinopathy of prematurity, intraventricular hemorrhage (≥Grade 3), surgical ligation, and presence of PDA at discharge between conservatively-managed and medically-treated infants (p>0.05). Multivariate analysis including perinatal factors showed that medical treatment was associated with increased risk for mortality (OR 1.68, 95% Cl 1.01-2.80, p=0.046), but decreased risk for BPD or death (BPD/death) (OR 0.59, 95%Cl 0.37-0.92, p=0.022). The preferred treatment options were ibuprofen (intravenous 36%, oral 31%), and paracetamol (intravenous 26%, oral 7%). Infants who were treated with oral paracetamol had higher rates of NEC and mortality in comparison to other treatment options. Infants treated before postnatal day 7 had higher rates of mortality and BPD/death than infants who were conservatively managed or treated beyond day 7 (p=0.009 and 0.007, respectively). In preterm infants born at less than 29 weeks of gestation with moderate-to-large PDA, medical treatment did not show any reduction in the rates of open PDA at discharge, surgical or prematurity-related secondary outcomes. In addition to the high incidence of spontaneous closure of PDA in the first week of life, early treatment (<7 days) was associated with higher rates of mortality and BPD/death.